Variação bionômica e metabólica em três espécies de Drosophila submetidas a diferentes dietas - SANTOS, CAMILA HELOISE DOS (2020)
In nature, there is intra and interspecific variability in the Drosophila genus regarding the ability to exploit resources. Thus, this work aimed to evaluate the effects of four diets, the standard bananaagar (DPB) and three others with different proportions of carbohydrates and proteins (HPS, EPS and LPS), on adaptive and metabolic traits of three neotropical species of Drosophila: D. willistoni, D. maculifrons and D. ornatifrons. Thus, larvae of these species were reared in these diets and the following traits were evaluated: 1) viability, determined as the percentage of pupae (VLP) and adults (VLA) that emerged from the second instar larvae submitted to the diets; 2) development time, estimated as the mean period (in hours) between the larvae transfers and the appearance of pupae (TLP) and adults (TLA); 3) dry weight of adult flies that have recently emerged from diets (only in chapter 1); and, 4) content of three metabolic energy storage molecules - triglycerides, glycogen and total soluble proteins. Metabolic pools were quantified by colorimetric assays using recently emerged adult flies from the diets. In chapter 1, in which only the standard banana diet was used, D. willistoni showed significant differences with D. maculifrons and D. ornatifrons for all the analyzed traits, except for the glycogen content, while D. maculifrons and D. ornatifrons only differed with respect to dry weight and triglyceride content. Drosophila ornatifrons showed differences between populations for all traits analyzed, D. maculifrons did not show a population difference only for viability and D. willistoni, in addition to viability, the development time was also not different between populations. For the other traits, dry weight and metabolites, D. maculifrons and D. ornatifrons presented the same pattern of population differentiation, whereas for D. willistoni the population pattern was opposite to that of the other two species, except for the content of triglyceride. In chapter 2, in which the other trhee diets were tested, Drosophila willistoni was viable in all tested diets, while D. maculifrons was not viable in LPS, and D. ornatifrons showed very low viability in this diet. The development time of D. willistoni increased only in the LPS diet, did not vary in D. maculifrons, and an increase in D. ornatifrons as higher the carbohydrate concentration was the diet. In D. willistoni, by trivariate analysis, only glycogen responded to the increase in carbohydrate in the diet, being found at higher levels in individuals fed with LPS. In D. maculifrons, the content of the three metabolites did not show any relationship with the carbohydrate and protein levels of the diets. In D. ornatifrons, the variation of carbohydrates and proteins in the diet had a more evident effect on triglyceride and protein levels. Also, interpopulation variations in several traits were found in all species, trade-offs were detected between viability and development time (D. willistoni and D. ornatifrons), development time and glycogen content (D. maculifrons and D. ornatifrons) and between glycogen and triglyceride contents (D. maculifrons), and positive correlations between viability and glycogen (D. ornatifrons) and between triglycerides and total proteins (D. maculifrons). Thus, we concluded that the variations in the concentrations of macronutrients in the diets tested in the present work, exerted differential pressures on the different traits evaluated, demonstrating that the evolutionary history and differential adaptations to the environments are important to define the amplitude of response that the species can show.